Parathyroid hormone, aldosterone-to-renin ratio and fibroblast growth factor-23 as determinants of nocturnal blood pressure in primary hyperparathyroidism: the eplerenone in primary hyperparathyroidism trial - Verheyen, Nicolas; März, Winfried (Journal of hypertension, 2016)
Objectives: The high prevalence of arterial hypertension in primary hyperparathyroidism (pHPT) is largely unexplained. Apart from parathyroid hormone (PTH), the mineral hormones fibroblast growth factor (FGF)-23 and aldosterone-to-renin ratio (ARR) are upregulated in pHPT. We aimed to determine whether nocturnal blood pressure (BP) is related with PTH, FGF-23 or ARR in a relatively large sample of pHPT patients. Methods: Cross-sectional data of the single-center “Eplerenone in Primary Hyperparathyroidism” trial were used. All patients with a biochemical diagnosis of pHPT who had both available 24-h ambulatory BP monitoring and valid laboratory data were included. Results: Full data were available in 136 patients (mean age 67 ± 10 years, 78% women). Median PTH was 99 (interquartile range: 82-124) pg/ml and mean calcium was 2.63 ± 0.15 mmol/l. ARR, but not PTH or FGF-23, was significantly and directly related with nocturnal SBP (Pearson's r = 0.241, P < 0.01) and DBP (r = 0.328, P < 0.01). In multivariate regression analyses, with adjustment for age, sex, PTH, FGF-23, traditional cardiovascular risk factors, antihypertensive medication and parameters of calcium metabolism ARR remained significantly and directly related with nocturnal BP (SBP: adjusted β-coefficient = 0.289, P < 0.01; DBP: β = 0.399, P < 0.01). The relationship between ARR and nocturnal SBP was exclusively present in patients with PTH levels above the median of 99 pg/ml. Conclusion: ARR, but not FGF-23 or PTH, was independently and directly related with nocturnal BP parameters in patients with pHPT, and this relationship was dependent on pHPT disease severity. Inappropriately, elevated aldosterone may partially explain the high prevalence of arterial hypertension in pHPT.
Gesehen am 21.09.2019